2009
DOI: 10.2135/cropsci2008.06.0355
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Plant Growth and Development in two Cotton Rotations under Irrigated and Non‐Irrigated Conditions

Abstract: Incorporating perennial grasses such as bahiagrass (Paspalum notatum Fluegge) to diversify the conventional two‐crop rotation of peanut (Arachis hypogaea L.) and cotton (Gossypium hirsutum L.) prevalent in the U.S. Southeast (SE) is advocated. However, little is reported on growth and development for cotton grown in rotation with perennial grasses. Our objectives were to compare plant characteristics including height, leaf area index (LAI), chlorophyll meter readings (chlorophyll index), N uptake, weed densiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 19 publications
1
9
0
Order By: Relevance
“…A long-term experiment was established in Quincy, FL, in 1999 to compare the proposed sodbased rotation with the conventional peanut-cotton rotation. The results of this experiment demonstrated that peanut and cotton yields were similar or higher in the sod-based rotation than they were in the conventional peanut-cotton rotation (Katsvairo et al 2007(Katsvairo et al , 2009. Additionally, in the cotton phase weed populations in the sod-based rotation were lower than in the conventional rotation (Katsvairo et al 2009).…”
mentioning
confidence: 72%
See 2 more Smart Citations
“…A long-term experiment was established in Quincy, FL, in 1999 to compare the proposed sodbased rotation with the conventional peanut-cotton rotation. The results of this experiment demonstrated that peanut and cotton yields were similar or higher in the sod-based rotation than they were in the conventional peanut-cotton rotation (Katsvairo et al 2007(Katsvairo et al , 2009. Additionally, in the cotton phase weed populations in the sod-based rotation were lower than in the conventional rotation (Katsvairo et al 2009).…”
mentioning
confidence: 72%
“…In north Florida, row-crop growers rely predominantly on a peanut-cotton rotation (Katsvairo et al 2009). The peanut phase lasts generally a single year and is followed by 2 yr of consecutive cotton (Zhao et al 2009).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…They did see a rotation yield response to increased N and P fertilizer. In other research, Katsvairo, Wright, Marois, Rich, and Wiatrak (2009) showed that cotton with Bahia grass rotations reduced weed densities and increased plant height, leaf area index, and N, P, and K uptake. However, with all these crop phenology increases, yield did not increase compared with conventional rotations with peanut.…”
Section: Yield By Crop Rotationmentioning
confidence: 90%
“…LTEs and strip plot designs are both schemes followed in agriculture and other field experiments, but, to our knowledge, a complete analysis of data coming from a long-term strip plot design of experiments is absent in the literature. Even if the experiment was conducted according to a long-term strip plot one, data are not analyzed appropriately [5], for example, consider an experiment where treatments were arranged in a strip plot design and observed over six years, but separate analyses for each year are presented. Federer and King [4] describe how to combine results from a strip plot experiment over several sites, but the approach cannot be immediately extended to the case of several years (long-term), though theoretically considered by the authors at the beginning of the book chapter.…”
Section: Long-term Strip Plotmentioning
confidence: 99%